2009
DOI: 10.1261/rna.1374809
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and structural analysis of base substitutions in the central pseudoknot of Thermus thermophilus 16S ribosomal RNA

Abstract: Characterization of base substitutions in rRNAs has provided important insights into the mechanism of protein synthesis. Knowledge of the structural effects of such alterations is limited, and could be greatly expanded with the development of a genetic system based on an organism amenable to both genetics and structural biology. Here, we describe the genetic analysis of base substitutions in 16S ribosomal RNA of the extreme thermophile Thermus thermophilus, and an analysis of the conformational effects of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…T. thermophilus ribosomes were used because of their ability to produce crystals that are amenable for X-ray structure determination (25). One of the two 16S rRNA genes (rrsB) was first replaced with the mutant allele, and then the other (rrsA) was replaced with the null allele ΔrrsA::htk1, marked with the high-temperature kanamycin resistance 1 gene (26). In both Escherichia coli (strain Δ7 prrn) and T. thermophilus, G299A conferred a larger growth defect than G347U.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T. thermophilus ribosomes were used because of their ability to produce crystals that are amenable for X-ray structure determination (25). One of the two 16S rRNA genes (rrsB) was first replaced with the mutant allele, and then the other (rrsA) was replaced with the null allele ΔrrsA::htk1, marked with the high-temperature kanamycin resistance 1 gene (26). In both Escherichia coli (strain Δ7 prrn) and T. thermophilus, G299A conferred a larger growth defect than G347U.…”
Section: Resultsmentioning
confidence: 99%
“…T. thermophilus strains expressing homogeneous populations of mutant ribosomes were constructed as follows. A ∼1,500-bp DNA fragment that includes the 5′ two-thirds of rrsB and adjacent DNA upstream was amplified from the T. thermophilus genome and cloned into pUC18-htk1, a vector encoding a thermostable kanamycin adenyltransferase (26,43). The resulting plasmid pMD3 was subjected to sitedirected mutagenesis to produce the derivatives pMD5 and pMD6, with mutations corresponding to 16S rRNA substitutions G347U and G299A, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As the replication origin of pUC-derived plasmids is not active in T. thermophilus, transformation with the knockout constructs to Kan r results from homologous recombination between the UHR and DHR with their respective chromosomal sequences. In contrast to findings with E. coli (38,39), double crossovers work very efficiently in T. thermophilus, without the need to select for single insertions and subsequent cointegrate resolution (17,35,40). While the latter approach does have the advantage of allowing the use of a single plasmid construct for insertion of pheS and its replacement, our preference is to construct an intermediate double-crossover strain as it allows replacement by transformation with genomic DNA as well as plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…The T. thermophilus HB27 genome produces 16S rRNA from two loci (rrsA and rrsB) that are unlinked to two rRNA operons, each encoding 23S rRNA (rrlA or rrlB), 5S rRNA (rrfA), and tRNA GCC Gly (glyT) as first described by Hartmann and Erdmann (41) and later indicated by the completed genome sequence (5). Our previous studies have shown that T. thermophilus is capable of surviving on a single rrs gene (35). Such deletion strains facilitate the genetic analysis of rRNA genes and allow the isolation of mutants with recessive antibiotic resistance mutations (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation